Dietary risk factors for inflammatory bowel diseases in a high‐risk population: Results from the Faroese IBD study. Issue 7 (1st August 2019) - Hammer, T; Lophaven, S Nymand; Nielsen, K Rubek; Petersen, M Skaalum; Munkholm, P; Weihe, P; Burisch, J; Lynge, E
Abstract : Background: The Faroe Islands currently have the highest recorded inflammatory bowel disease (IBD) incidence in the world. Objective: This study investigated environmental risk factors for IBD in the Faroese population. Methods: Environmental exposure data including lifestyle risk factors and neurotoxicants collected for over 30 years were retrieved from the Children's Health and the Environment in the Faroes (CHEF) cohorts including mainly mother–child pairs, with exposure data collected from pregnant mothers. For lifestyle risk factors, the incidence of IBD and ulcerative colitis (UC) was calculated as the rate ratio (RR) with 95% confidence intervals (CI) in exposed versus non‐exposed persons. For neurotoxicants RR was calculated for persons with high versus low exposure. Results: Six cohorts included 5698 persons with complete follow‐up data and at least one exposure, and 37 were diagnosed with IBD. For pilot whale/blubber, the RR was 1.02 (95% CI, 0.48–2.18); RR of 1.01 for fish (95% CI, 0.35–2.91); and of the pollutants studied, a statistical significantly increased risk was found for 1, 1, 1, ‐trichloro‐2, 2‐bis‐(p‐chlorophenyl) ethane (p, p'‐DDT); RR 3.04 (95% CI, 1.12–8.30). RRs were 1.96 (95% CI, 1.03–3.73) for smoking and 1.10 (95% CI, 0.55–2.19) for alcohol intake. Conclusion: The high IBD incidence is unlikely to be caused by special dietary habits or by environmental pollutants.